2022
DOI: 10.1039/d2ra01763f
|View full text |Cite
|
Sign up to set email alerts
|

A mechanistic study on electro-Fenton system cooperating with phangerochate chrysosporium to degrade lignin

Abstract: The combined catalytic system of Electro-Fenton (E-Fenton) and Phanerochaete chrysosporium (P. chrysosporium) was constructed in liquid medium with additional potential to overcome the limitations of lignin degradation by white rot fungi alone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 52 publications
0
1
0
Order By: Relevance
“…The results demonstrated that Mn 2 L 2 (H 2 O) 2 (N­(CN) 2 ) 2 could be utilized for the electrocatalytic oxidation of veratrol, with the best electrocatalyst conversion rate of up to 85%. Qin et al combined enzyme catalysis and an electro-Fenton system, developing an electrocatalytic oxidation system with a liquid medium using electro-Fenton and Chrysophora. The system achieved better catalytic effects on lignin than white rot fungi alone.…”
Section: Electrocatalytic Upgrade Of Lignin From the Perspective Of U...mentioning
confidence: 99%
“…The results demonstrated that Mn 2 L 2 (H 2 O) 2 (N­(CN) 2 ) 2 could be utilized for the electrocatalytic oxidation of veratrol, with the best electrocatalyst conversion rate of up to 85%. Qin et al combined enzyme catalysis and an electro-Fenton system, developing an electrocatalytic oxidation system with a liquid medium using electro-Fenton and Chrysophora. The system achieved better catalytic effects on lignin than white rot fungi alone.…”
Section: Electrocatalytic Upgrade Of Lignin From the Perspective Of U...mentioning
confidence: 99%